Toward a unified hydrous olivine electrical conductivity law. (29th December 2014) - Gardés, Emmanuel; Gaillard, Fabrice; Tarits, Pascal
Abstract It has long been proposed that water incorporation in olivine has dramatic effects on the upper mantle properties, affecting large‐scale geodynamics, and triggering high electrical conductivity. But the laboratory‐based laws of olivine electrical conductivity predict contrasting effects of water, precluding the interpretation of geophysical data in term of mantle hydration. We review the experimental measurements of hydrous olivine conductivity and conclude that most of data are consistent when errors in samples water contents are considered. We report a new law calibrated on the largest database of measurements on hydrous olivine oriented single crystals and polycrystals. It fits most of measurements within uncertainties, and is compatible with most of geophysical data within petrological constraints on mantle olivine hydration. The conductivity anisotropy of hydrous olivine might be higher than dry olivine, but preferential orientation should produce moderate anisotropy (∼0–0.8 log unit). In the oceanic mantle, the enhancement of olivine conductivity is limited to ∼1 log unit in the maximum range of mantle olivine water concentrations (0–500 wt ppm). Strongest enhancements are expected in colder regions, like cratonic lithospheres and subduction settings. High conductivities in melt‐free mantle require great depths and high water concentrations in olivine (>0.1 S/m at >250 km and >200 wt ppm). Thus, the hydration of olivine appears unlikely to produce the highest conductivities of the upper mantle.